Kristologi Humanis dan Diskriminatif bagi Etnis Tionghoa - Patty, Martha Marselina (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2023)
Racial discrimination generally arises from the perceived superiority of one particular ethnicity over other ethnicities. This is what happens to ethnic Chinese in Indonesia. Discrimination against ethnic Chinese is a phenomenon that has been going on for quite a long time. This can be seen from the cases of riots from 1998 to 2020, also when the Covid-19 pandemic hit the world which also hit Indonesia. This discrimination against ethnicity is carried out in verbal and physical form. This article aims to offer a humanist Christology of Jesus as a point of view on the problem of discrimination as stated above. The method used is library research which examines selected Christian texts and extracts and concludes them as a humanist attitude of Jesus. This research found that Jesus' good attitude towards people who were marginalized and looked down upon by other groups shows that Jesus began to build bridges for relations between humans regardless of ethnicity, religion,race and between groups. This research concludes that Jesus was very pro-humanity, He did not view other ethnicities as